The effect of cash flow, size and financial sustainability ratio on tobin's q through dividend payout ratio in companies in idx high dividend 20 years 2021-2023 - Priatsaleh, Disti Paremono; Nurwulandari, Andini (Enrichment : Journal of Management, 2025)
The phenomenon that occurs in this study is that every year not all companies that are included in the IDX High Dividend 20 (IDXHIDIV20) are always there in each year, many companies take turns entering the IDX High Dividend 20 (IDXHIDIV20) even though there are also companies that are always included in the IDX High Dividend 20 (IDXHIDIV20) from the span of 2021-2023. This study examines the effect of liquidity, company size, and financial sustainability on firm value through dividend policy in companies listed in the IDX High Dividend 20 for the period 2021-2023. This study aims to analyse the direct and indirect effects of liquidity, firm size, and financial sustainability on firm value, considering dividend policy as a mediating variable. Using a quantitative approach, data was collected from companies that consistently appeared in the IDX High Dividend 20 during the specified period. This study uses multiple regression analysis to test the proposed hypotheses using SEM-PLS software. The results showed that Liquidity has an effect on firm value; Firm size has no effect on firm value; Financial sustainability has an effect on firm value; Dividend policy has an effect on firm value; Liquidity has no effect on dividend policy; Firm size has an effect on dividend policy; Financial sustainability has an effect on dividend policy; Dividend policy is unable to mediate Liquidity on firm value; Dividend policy is able to mediate Firm size on firm value; Dividend policy is able to mediate Financial sustainability on firm value. The implications of these findings provide valuable insights for corporate management in making strategic decisions and for investors in evaluating the potential of companies with high dividends. Further research can explore the role of other financial metrics and external factors in influencing firm value in different sectors or markets